Can anyone help me with this functional equation:

\(f(f\left( x+y \right) )\quad =\quad x\quad +\quad f(y)\quad \)

I'm quite new to the topic so if anyone has any resources, I would be very grateful!

Thanks

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestput x=0 to get f(f(y)) = f(y) therefore f(f(x+y)) = f(x+y) = x + f(y) put y=0 to get f(x) = x + a for some constant a. putting this back in the problem, 2a=a and so f(x) = x for all real x..

Log in to reply